PECULIARITIES OF GOODS IDENTIFICATION IN EXPORT AND IMPORT OPERATIONS - PAKHOLIUK, Olena; DZIUBYNSKYI, Andriy; PEREDRIY, Oksana; MARTOSENKO, Marina (Herald of Khmelnytskyi National University. Economic sciences, 2023)
In the course of export and import operations, the identification of goods plays an important role in ensuring the correct execution of customs declarations, compliance with customs regulations, and determining the rate of customs duties and other payments. Identification is a preliminary stage of the classification of goods and is important in shaping the flow of goods, accelerating customs procedures and improving their efficiency. It should be noted that a purely commodity-based approach to the classification of goods will be somewhat different from the customs approach, as the customs approach must adhere to the basic rules of interpretation of the explanations, exceptions and notes to sections and groups, terminology, and must take into account the properties, signs, indicators and methods of determination that are accepted as determinative and recommended when identifying classification groups. Despite the existence of many scientific works on the topic of this study, the essence of identification as a component of the process of export-import operations in Ukraine has not yet been clarified, aspects of the current state of functioning have not been identified, and ways of modernisation and means of identification of goods in export-import operations have not been proposed. The purpose of this study is to analyse the current state of affairs and to provide recommendations on how to create effective and reliable procedures for the identification of goods in order to improve export-import operations and ensure compliance with legislation and technical regulations. Thus, the identification of goods in the course of export-import operations is a set of actions of customs officials aimed at controlling the information on the customs value of goods transported across the customs border of Ukraine, with mandatory verification of accompanying documents for such goods and information on the counterparties to foreign economic transactions under which certain export-import operations were carried out.